Bearing strength of shear connections for tubular structures: An analytical approach. (June 2018) - Latour, M.; Rizzano, G.; D'Antimo, M.; Demonceau, J.F.; Jaspart, J.P.; Armenante, V.
Abstract: This work deals with the prediction of the bearing resistance of elementary shear connections constituted by gusset plates and square hollow sections fastened with long bolts. The research is motivated by the lack of specific rules in international codes for this particular configuration. In fact, while in lap shear connections, single or double-sided, the holes are always confined out of plane, in case of connections with long bolts and gusset plates (typical of tubular structures), the holes are constrained out of plane outwards, but they are free to buckle inwards, providing a reduction of the bearing strength. Within this framework, the paper is aimed at the development of an analytical formulation for the prediction of the bearing resistance of connections with long bolts and square hollow sections (SHS). The proposal is based on the calculation of the post-buckling load of the tube plate subjected to bearing at the bolt hole, combining the Winter's formula (originally developed to predict the post-buckling strength of steel plates accounting for geometrical and mechanical imperfections) with a simplified FE model developed in SAP 2000. The procedure developed is presented in detail proposing a design equation for connections with long bolts, based on a formula suggested recently by Može (2014, 2016) suitable for the inclusion in code provisions such as EC3. The accuracy of the design equation is checked on the experimental data reported in a previous work of the same authors properly extended with parametric FE simulations to cope for variation of geometrical parameters. Highlights: The paper proposes a design equation for bearing strength of tubular structures. An extension of the equation recently suggested by Može is proposed. A procedure to calculate the elastic buckling load of the bolt hole is defined. A correction coefficient for connections with long bolts is determined. The design formula is validated against test data showing a satisfactory accuracy.